Micellar paclitaxel in the treatment of patients with tumors of the female reproductive system - A. G. Kedrova; S. E. Krasilnikov; D. A. Astakhov; V. V. Kosyy (ABV-press, 2019)
Background. Treatment of patients with advanced cancers of the female reproductive system is very challenging. The most common treatment scheme for such patients includes paclitaxel 135-175 mg/m2 + carboplatin AUC 5-6 or cisplatin 75 mg/m2. However, lengthy treatment with this regimen is limited by adverse events, such as neuropathy, allergic reactions, nephropathy, etc. The new micellar form of paclitaxel has demonstrated better tolerability compared to conventional paclitaxel and, considering the increased safe effective dose (up to 250 mg/m2) it should ensure higher efficacy and better progression-free survival. The use of cremophor EL free paclitaxel is recommended in patients with concomitant extragenital diseases (including diabetes and neurological deficit), in elderly patients, and in patients with allergic reactions, as well as in cases when additional steroids should be avoided.Objective: to summarize the experience of using the new form of paclitaxel in patients with tumors of the female reproductive system and concomitant diseases.Materials and methods. We analyzed both world and our own experience in using micellar paclitaxel at a dose of200-250 mg/m2 administered as a 1-hour intravenous infusion every 21 days for 3-6 treatment cycles in patients with solid tumors of the female reproductive system.Results. The polymeric micellar composition of cremophor EL free paclitaxel can be used in higher therapeutic doses with a lower risk of hypersensitivity and peripheral neurotoxicity. Fatigue and neuropathy were the most common dose-dependent adverse events of this drug. Nonew adverse reactions unknown for paclitaxel have been registered.Conclusions. The possibility of administration of micellar paclitaxel without premedication with steroids or at a minimum dose* makes it a promising candidate for further studies in combination with new targeted drugs and immunotherapy.